Sport tourism : concepts and theories - Gibson, Heather J. (Heather Julie), ....- (New York : Routledge, 2006)
The study of sport tourism is on the cusp of moving from a descriptive phase of research into an analytical phase. Consequently, many academics and graduate students are searching for theories upon which to ground their work. This book draws upon theories and concepts from sociology and anthropology (the socio-cultural perspective), sport and tourism studies, and business studies. One of the dangers of a new area of study is that the body of knowledge is built on a range of seemingly unrelated studies. By grounding work in a theoretical perspective, future work can be linked to, and contribute to building a cohesive understanding of various aspects of sport tourism. This book is an edited collection written by some of the top scholars working in a particular domain throughout the world, providing a compendium of theories and concepts that can be used to frame research on various aspects of sport tourism.
Sport tourism: concepts and theories. An introduction / Heather Gibson -- Part One. Understanding sport tourism: socio-cultural perspectives. 1. Leisure constraint theory and sport tourism / Tom Hinch, ... [et al.] -- 2. Serious leisure, social identity and sport tourism / Ian Jones and B. Christine Green -- Something lived, something learned: nostalgia's expanding role in sport tourism / Sheranne Fairley and Sean Gammon -- Part Two. Sport and tourist studies: theories and paradigms. 4. Towards an understanding of 'why sport tourists do what they do' / Heather Gibson -- 5. Building sport event tourism into the destination brand: foundations for a general theory / Laurence Chalip and Carla Costa -- 6. Sport tourism as an attraction for managing seasonality / James Higham -- 7. Host and guest relations and sport tourism / Elizabeth Fredline -- 8. Sport tourism, cityscapes and cultural politics / Michael Silk and John Amis -- Part Three. Business studies: concepts and paradigms. 9. Marketing sport tourism: creating synergy between sport and destination / Tracey Harrison-Hill and Laurence Chalip -- 10. Service quality perspectives in sport tourism / Des Thwaites and Simon Chadwick -- 11. Public sector support for sport tourism events: the role of cost-benefit analysis / Trevor Mules and Larry Dwyer -- 12. A grounded theory of the policy process for sport and tourism / Mike Weed -- 13. The management of sport tourism / Margaret Deery and Leo Jago -- Conclusion.
This volume was previously published as a special issue of the journal Sport in the Global Society.
Includes bibliographical references and index.
Keywords: Sporttoerisme; Sports and tourism